The relationship between corporate social responsibility and company's financial performance: the case of Top One Hundred Companies in Malaysia - Adamu, Muhammad Sani (2015)
Since the inception of companies’ activity in Malaysia, the value of corporate social responsibility (CSR) has been an important topic in accounting research. Despite extensive studies on CSR activities in Malaysia, studies investigated the nature of CSR activities in relation to firm financial performance was limited. Thus, this research investigates and analyzed the current nature of CSR activities and the relationship between CSR activities and firm financial performance of Malaysian public listed companies. This research relied on secondary data that were obtained through the content analysis of published company’s annual reports for the year 2009 to 2013. Based on purposive sampling method, this study covered the assessment of the top one hundred companies in Malaysia whose names and shares were quoted in Malaysia stock exchange (Bursa Malaysia). Based on literature, four independent variables (Environment, Community, Workplace and Marketplace) and two dependent variables, Earning per Share (EPS), and Return on Equity (ROE) have been chosen in this study. Data were analyzed and interpreted using three types of data analysis; descriptive statistics, ttest and Pearson’s correlation, to investigates the current nature as well as to analyzed the relationship between CSR activities and firm financial performance. This research discovered that since 2009 to 2013, Top 100 companies in Malaysia have been involved in CSR activities especially in the area of Community activities followed by Environmental activities, Workplace activities and finally, Marketplace activities. In term of their relationship with financial performance, this research shows that there is positive relationship between the independent variables and the dependent variables. It also concluded that, the extent of innovation and conformity with CSR framework in Malaysia has improved the quality of financial report that is capable of competing in global scene.